2010
DOI: 10.1111/j.1464-5491.2010.02938.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of efficacy and safety of vildagliptin and gliclazide in combination with metformin in patients with Type 2 diabetes inadequately controlled with metformin alone: a 52‐week, randomized study

Abstract: In patients with Type 2 diabetes inadequately controlled with metformin, addition of vildagliptin provided similar HbA(1c)-lowering efficacy compared with gliclazide after 52 weeks of treatment. Although both treatments were well tolerated, vildagliptin-treated patients had fewer hypoglycaemic events and did not gain weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(49 citation statements)
references
References 29 publications
3
36
0
9
Order By: Relevance
“…However, in the present review, only head-to-head trials vs active comparators are presented in brief. Gliptins have also been compared with SUs (glimepiride, glipizide, gliclazide) [27][28][29][30][31][32][33][34], TZDs (pioglitazone 30 mg, rosiglitazone 8 mg) [35][36][37][38][39] and GLP-1 receptor agonists (exenatide, liraglutide) [36,40,41]. However, only one head-to-head study compared two different DPP-4 inhibitors in the same trial: saxagliptin 5 mg with sitaglitptin 100 mg as add-ons to basal metformin therapy [42].…”
Section: Gliptins Combined With Metforminmentioning
confidence: 99%
“…However, in the present review, only head-to-head trials vs active comparators are presented in brief. Gliptins have also been compared with SUs (glimepiride, glipizide, gliclazide) [27][28][29][30][31][32][33][34], TZDs (pioglitazone 30 mg, rosiglitazone 8 mg) [35][36][37][38][39] and GLP-1 receptor agonists (exenatide, liraglutide) [36,40,41]. However, only one head-to-head study compared two different DPP-4 inhibitors in the same trial: saxagliptin 5 mg with sitaglitptin 100 mg as add-ons to basal metformin therapy [42].…”
Section: Gliptins Combined With Metforminmentioning
confidence: 99%
“…In total,19 studies were included in the base case analysis at 24-weeks ± 6 weeks [7,23,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table S2) and a further 4 were eligible for the sensitivity analysis due to timeframe (± 8 weeks) and quality issues (Table S4). Of the 15 studies reporting data at the 52-week time point, 8 were included in the base case analysis [8,[42][43][44][45][46][47][48] (Table S3) with the remaining 7 assessed in the sensitivity analysis for the same reasons (timeframe and quality issues) (Table S4). Two included studies presented outcomes at both 24-and 52-weeks [23,24] and one study reported data from two citations [23,57].…”
Section: Systematic Review Search Resultsmentioning
confidence: 99%
“…Vildagliptin may be used as monotherapy, but better results are found when it is combined with metformin (12,13). Recent studies have shown that, as add-on therapy in patients with inadequately controlled T2DM treated with metformin, vildagliptin was as effective as TZDs (19) and sulphonylureas (20,21). In the present study, we observed that addition of vildagliptin to an unsuccessful combination of metformin with sulphonylurea was able to reduce HbA1c to < 7.0% in 29.7% of patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%